Ethical reasoning and participatory approach towards achieving regulatory processes for animal-visitor interactions (AVIs) in South Africa. - Alessia Muzzo; Ilaria Pollastri; Pierfrancesco Biasetti; Gregory Vogt; Raoul Manenti; Barbara de Mori (PLoS ONE, 2023)
South Africa's wide range of animal facilities offers many different types of Animal-Visitor Interactions, wild animal encounters where animals and visitors come closer than in normal circumstances. The aim of this study was to provide a map of the ethically relevant aspects involved in AVIs in South Africa as a first step towards regulating these activities. A participative approach based on the ethical matrix, a tool which organizes the ethical standings of the stakeholders by three bearing ethical principles (wellbeing, autonomy, fairness), was applied. The matrix was populated through a top-down approach and refined by engaging stakeholders in a workshop and two online self-administrated surveys. The outcome is a map of the value demands concerning Animal Visitor Interactions. This map shows how the ethical acceptability of AVIs is linked to different relevant issues like animal welfare, education, biodiversity conservation, sustainability, human competency, facility mission, impact on scientific research and socio-economic outcomes. In addition, results highlighted the importance of cooperation among stakeholders and suggested that attention for animal welfare can inform decision making and inspire a multidisciplinary approach in implementing a regulatory frame for South African wildlife facilities.